A novel bioactivity of andrographolide from Andrographis paniculata on cerebral ischemia/reperfusion-induced brain injury through induction of cerebral endothelial cell apoptosis. (September 2013) - Yen, Ting-Lin; Hsu, Wen-Hsien; Huang, Steven Kuan-Hua; Lu, Wan-Jung; Chang, Chao-Chien; Lien, Li-Ming; Hsiao, George; Sheu, Joen-Rong; Lin, Kuan-Hung
Abstract Context: Andrographolide, extracted from the leaves of Andrographis paniculata (Burm. f.) Nees (Acanthaceae), is a labdane diterpene lactone. It is widely reported to possess anti-inflammatory and antitumorigenic activities. Cerebral endothelial cells (CECs) play a crucial role in supporting the integrity and the function of the blood–brain barrier (BBB). However, no data are available concerning the effects of andrographolide in CECs. The aim of this study was to examine the detailed mechanisms of andrographolide on CECs. Objective: This study investigated a novel bioactivity of andrographolide on cerebral ischemia/reperfusion-induced brain injury. Materials and methods: CECs were treated with andrographolide (20–100 µΜ) for the indicated times (0–24 h). After the reactions, cell survival rate and cytotoxicity were tested by the MTT assay and the lactate dehydrogenase (LDH) test, respectively. Western blotting was used to detect caspase-3 expression. In addition, analysis of cell cycle and apoptosis using PI staining and annexin V-FITC/PI labeling, respectively, was performed by flow cytometry. We also investigated the effect of andrographolide on middle cerebral artery occlusion (MCAO)/reperfusion-induced brain injury in a rat model. Results: In the present study, we found that andrographolide (50–100 µΜ) markedly inhibited CEC growth according to an MTT assay and caused CEC damage according to a LDH test. Our data also revealed that andrographolide (50 µM) induced CEC apoptosis and caspase-3 activation as respectively detected by PI/annexin-V double staining and western blotting. Moreover, andrographolide arrested the CEC cell cycle at the G0/G1 phase by PI staining. In addition, andrographolide (5 mg/kg) caused deterioration of MCAO/reperfusion-induced brain injury in a rat model. Conclusions: These data suggest that andrographolide may disrupt BBB integrity, thereby deteriorating MCAO/reperfusion-induced brain injury, which are, in part, associated with its capacity to arrest cell-cycle and induce CEC apoptosis.